Enhanced Plasma H2S Levels Associated With Fasting Blood Glucose In Type-2 Diabetes Mellitus - Saha, Pinaki; Banerjee, Piyasa; Pal, Prasenjit; Auddya, Lakshmisona; Sen, Santanu; Sau, Tanmay Jyoti; Kumar, Arun; Biswas, Utpal Kumar (Asian Journal of Medical Sciences, 2015)
Introduction: A number of recent literatures suggest a potential role of H2S and H2S modifying agents in the etiology and management of type-2 diabetes mellitus. Objective: The current study was aimed to evaluate the plasma levels of H2S in the patients with type 2 Diabetes mellitus and to find out if there is any relationship of H2S concentrations with the fasting blood glucose levels. Methods: Plasma H2S levels were measured in sixty two recently diagnosed type 2 diabetic patients and compared with similar number of healthy volunteers as controls. Results: The plasma H2S level in the patients ( 81.17 ± 16.40 micromol/l ) is significantly higher (P< 0.001) than the healthy controls (50.69 ± 8.69 micromol/l) and the H2S levels in plasma have significant positive correlation (r= 0.359, P=0.004) with fasting blood glucose levels. Conclusion: The present study has elucidated that the patients with type-2 diabetes mellitus are associated with elevated plasma H2S levels which are well correlated with glucose levels. This reveals a potential the role of H2S modulators towards the management of this non-communicable epidemic disorder. DOI: http://dx.doi.org/10.3126/ajms.v6i6.12532 Asian Journal of Medical Sciences Vol.6(6) 2015 11-15